METODE FUZZY UNTUK MENENTUKAN KELAYAKAN AGEN SEMEN (STUDI KASUS CV. GANESHA JAYA MANDIRI) - Ramadhani Ramadhani (JUSIM (Jurnal Sistem Informasi Musirawas), 2022)
Padang Cement is the oldest cement factory Indonesia. n marketing cement to various regions, PT. Semen Padang collaborates a lot with distributors. and it is from this distributor that cement reaches various regions. This study aims to examine the feasibility of agents from distributors to become cement agents. In this study, determining this feasibility is limited by two indicators, namely capital and demand and using the Mamdani method of Fuzzy logic.